2006
DOI: 10.1001/archneur.63.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Quantitative Indexes of Concurrent α-Synuclein Abnormalities to Clinical Outcome in Autopsy-Proven Alzheimer Disease

Abstract: Background: Lewy bodies (LBs) and Lewy neurites are frequent concomitant neuropathologic observations in clinical and neuropathologically defined Alzheimer disease (AD), but their relation to clinical features in AD is uncertain. Most studies used semiquantitative measures to determine the presence or absence of LB abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…There have been numerous clinicopathological studies attempting to correlate amyloid plaques with the cognitive deficits seen in AD (Blessed et al, 1968; Tomlinson et al, 1970; Duyckaerts et al, 1990, 1998; Berg et al, 1998; Gold et al, 2000; Mungas et al, 2001; Tiraboschi et al, 2002, 2004; Guillozet et al, 2003; Kraybill et al, 2005; Holtzer et al, 2006; Markesbery et al, 2006; Nelson et al, 2007a, 2009a; Beach et al, 2009; Sabbagh et al, 2010; Robinson et al, 2011). Apparent inconsistencies in the conclusions of these studies are due to differences in study cohorts, methodology used to classify plaque subcategories, plaque-counting techniques, and metrics used to assess cognitive deficits.…”
Section: Overview Of Neuropathological Changes In Admentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous clinicopathological studies attempting to correlate amyloid plaques with the cognitive deficits seen in AD (Blessed et al, 1968; Tomlinson et al, 1970; Duyckaerts et al, 1990, 1998; Berg et al, 1998; Gold et al, 2000; Mungas et al, 2001; Tiraboschi et al, 2002, 2004; Guillozet et al, 2003; Kraybill et al, 2005; Holtzer et al, 2006; Markesbery et al, 2006; Nelson et al, 2007a, 2009a; Beach et al, 2009; Sabbagh et al, 2010; Robinson et al, 2011). Apparent inconsistencies in the conclusions of these studies are due to differences in study cohorts, methodology used to classify plaque subcategories, plaque-counting techniques, and metrics used to assess cognitive deficits.…”
Section: Overview Of Neuropathological Changes In Admentioning
confidence: 99%
“…In contrast to the literature concerning amyloid plaques, a large number of studies have arrived at a common finding, namely, there is a strong link between neocortical NFTs and cognitive decline (Tomlinson et al, 1970; Duyckaerts et al, 1990, 1997, 1998; Mckee et al, 1991; Arriagada et al, 1992; Bierer et al, 1995; Davis et al, 1995; Dickson et al, 1995; Nagy et al, 1995, 1999; Cummings et al, 1996; Berg et al, 1998; Grober et al, 1999; Sabbagh et al, 1999; Gold et al, 2000; Mungas et al, 2001; Riley et al, 2002; Silver et al, 2002; Tiraboschi et al, 2002; Guillozet et al, 2003; Bennett et al, 2004; Kraybill et al, 2005; Holtzer et al, 2006; Markesbery et al, 2006; Koepsell et al, 2008; Whitwell et al, 2008; Beach et al, 2009; Brayne et al, 2009; Giannakopoulos et al, 2009; Sabbagh et al, 2010; Robinson et al, 2011). It should be noted that outside of frontotemporal lobar degeneration (FTLD), one does not see widespread cortical NFTs without abundant plaque pathology.…”
Section: Overview Of Neuropathological Changes In Admentioning
confidence: 99%
“…The association between the occurrence of Lewy bodies in AD patients and disease severity is under debate. Some authors do not find any correlation; other papers are indicating that there is a link between the mixed pathology and an accelerated disease progression [91][92][93][94][95].…”
Section: Alpha Synuclein and Alzheimer's Diseasementioning
confidence: 96%
“…Holtzer et al [36] PD Aggregated a-synuclein in primary mesencephalic neuron-glia culture activated microglia that enhanced dopaminergic neurodegeneration Zhang et al [37] Autoantibodies MS Autoantibodies to myelin basic protein were detected in sera from patients with MS Hedegaard et al [38] AD Autoantibodies to b-amyloid are common in AD Kellner et al [39] ALS Autoantibodies to neurofilament are found in patients with ALS Couratier et al [40] PD Autoantibodies to a-synuclein were detected in patients with PD, particularly the familial form…”
Section: Parallels Between Ms and Neurodegenerative Diseasesmentioning
confidence: 99%